The Role of Digital Literacy and Family Support On The Success of Exclusive Breastfeeding Practices in Mothers Aged 20-35 Years in the Work Area Of Marisa Public Health Center - Ilham, Sartika; Ukik Agustina; Janik Kurniawati (Universitas STRADA Indonesia, 2025)
Digital literacy is the knowledge and skills of users in using digital media. Exclusive breastfeeding behavior is the knowledge, perception and attitude as well as real actions of mothers and their environment towards exclusive breastfeeding. In overcoming obstacles by finding the best solution so that they can continue to provide breast milk for up to 6 months. The study aims to determine the relationship between the role of digital literacy as a source of health information and family support for the success of Exclusive Breastfeeding practices. This research design uses a quantitative method with a cross-sectional epidemiological study approach. The population in this study were all mothers who had babies aged ≥6 Months - 2 Years with a maternal age range of 20-35 Years. The sampling technique used was a quota sampling technique. Data collection was in the form of an online questionnaire in the form of a google form link. The result of this research is the total 130 respondents, 91 respondents succeeded in providing exclusive breastfeeding while 37 other respondents were unable to provide exclusive breastfeeding to their babies. The test results showed (p = 0.646) that digital literacy did not have a significant role in the success of exclusive breastfeeding practices. While the results of the Chi-square analysis test on family support showed a value (p = 0.088) that family support also did not have a significant role in the success of exclusive breastfeeding practices. Other supporting factors are needed that must also play a role so that there is real action from the mother to provide exclusive breastfeeding.